(untitled) (Ameghiniana, 2018)
More than 40 remains of Tremacyllus Ameghino (Notoungulata, Hegetotheriidae, Pachyrukhinae) from the Province of La Pampa (Argentina) are analyzed. They were recovered from different outcrops of the late Miocene Cerro Azul Formation at Laguna Chillhué, Quehué, Telén, Salinas Grandes de Hidalgo, Estancia Ré, Bajo Giuliani, Barrancas Coloradas and Caleufú. During the late Miocene, pachyrukhines are represented by two genera, Tremacyllus and Paedotherium Burmeister. The present sample of Tremacyllus allows for the dental morphological variation to be evaluated, especially in lower and upper premolars. This study shows high variability in the diagnostic characters of two recognized species, T. impressus Ameghino (Pliocene–Pleistocene of the Pampean Region) and T. incipiens Rovereto (late Miocene of Catamarca). We interpret these differences to actually correspond to intraspecific variation and, consequently, propose their synonymy. T. impressus has priority over T. incipiens, and an emended diagnosis is provided. This nomenclatural action implies, in turn, the extension of the biochron of Tremacyllus impressus from the late Miocene to the Pleistocene. T. impressus differs from Paedotherium in its smaller size, post-incisive impressions extended beyond the level of P2 (even reaching the anterior margin of P3), M3 shorter or equal to M2, relatively shorter mandibular symphysis, and lower premolars not molariform and more imbricated. Within the studied sample, we identify several juvenile specimens that confirm the dental eruption pattern previously proposed for Tremacyllus based on fewer remains.